Nonlinear phenomena of a supercritical water heated channel natural circulation loop - Jin Der Lee; Shao Wen Chen (AIP Advances)
The passive feature of a supercritical natural circulation loop (NCL) has promising applications in various fields. The nonlinear natures of a NCL using supercritical water are explored by a dimensionless dynamic model developed in this study, particularly regarding the occurrence of instability. The results demonstrate that the outlet flow resistance of the heated channel will significantly influence the stability and nonlinear behaviors of this supercritical water NCL. Complex nonlinear phenomena would take place in the system while the heated channel is subject to a relatively large outlet flow resistance. A route toward chaotic oscillation can be evolved from periodic oscillations by means of period-doubling bifurcations. The examinations by fast Fourier transform analysis and sensitivity to initial conditions further confirm the existence of chaotic oscillation. The bifurcation phenomena can be inspected by the variations in the fundamental dimensionless frequencies of periodic oscillations. In addition, the indication of period three point implies that innumerable periodic and chaotic kinds of nonlinear oscillations can prevail in the unstable area of this supercritical water NCL under some specific operating conditions.